PENGARUH E-COMMERCE, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEBELIAN (STUDI PADA BATIK MAHKOTA LAWEYAN, SURAKARTA) - Khabibuddin Al Ghoribi; Handoyo Djoko Waloejo (Jurnal Ilmu Administrasi Bisnis, 2018)
This study aims to determine the influence of e-commerce, product quality, and product promotion on purchasing decisions of Mahkota Batik;s products in Laweyan, Surakarta. This was an explanatory research using questionnaires as the tools to collect the primary data. This study included 100 respondents as the sample and the data were taken with purposive sampling method and accidental technique. The selected respondents were those who have made purchases in Batik Mahkota and have conducted payment transactions using electronic instruments. The methodology used to analyze the primary data in this research was validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and significance test (t and F test) using SPSS 16.0. The results showed that e-commerce had a significant effect on purchasing decisions with a percentage of 27.4%, while the rest was influenced by factors other than e-commerce. Product quality significantly influenced the purchase decisions with a percentage of 33.2%, while the rest was influenced by factors other than product quality. Product promotion also had a significant effect on purchasing decisions with a percentage of 29.6%, while the rest was influenced by factors other than promotion. While simultaneously, e-commerce, product quality, and promotion had a significant effect on purchasing decisions with a percentage of 44.8%, while the rest was influenced by factors other than e-commerce, product quality, and promotion. It can be concluded that the better the e-commerce system used, product quality, and the promotion technique, the higher the purchase decision of the products of Batik Mahkota. Based on the results obtained in the research, researchers then suggested that Batik Mahkota should improve the e-commerce in terms of system’s quality and information’s quality. Maintaining and improving the product quality and planning on more promotional activities can also be done to make improvement.